Insight of the Interaction between 2,4-thiazolidinedione and Human Serum Albumin: A Spectroscopic, Thermodynamic and Molecular Docking Study - Rahman, Safikur (Int J Mol Sci, 2019)
Thiazolidinedione derivatives (TZDs) have attracted attention because of their pharmacological effects. For example, certain TZDs have been reported to ameliorate type II diabetes by binding and activating PPARs (peroxisome proliferator-activated receptors). Nonetheless, no information is available on the interaction between the heterocyclic 2, 4-thiazolidinedione (2,4-TZD) moiety and serum albumin, which could affect the pharmacokinetics and pharmacodynamics of TZDs. In this study, we investigated the binding of 2,4-TZD to human serum albumin (HSA). Intrinsic fluorescence spectroscopy revealed a 1:1 binding stoichiometry between 2,4-TZD and HSA with a binding constant (K(b)) of 1.69 ± 0.15 × 10(3) M(−1) at 298 K. Isothermal titration calorimetry studies showed that 2,4-TZD/HSA binding was an exothermic and spontaneous reaction. Molecular docking analysis revealed that 2,4-TZD binds to HSA subdomain IB and that the complex formed is stabilized by van der Waal’s interactions and hydrogen bonds. Molecular dynamics simulation confirmed the stability of the HSA-TZD complex. Further, circular dichroism and 3D fluorescence studies showed that the global conformation of HSA was slightly altered by 2,4-TZD binding, enhancing its stability. The results obtained herein further help in understanding the pharmacokinetic properties of thiazolidinedione.